Exploration of Aflatoxin B1 Degradation Products via Kocuria rosea: Structure Elucidation and Toxicity Analysis - Jingying Wang; Jun Nan; Qiqi Chen; Ying Zhou; Xiujun Gao; Yuexin Li (Applied Sciences)
Aflatoxin B1, a natural mycotoxin produced by Aspergillus fungi with high toxicity and carcinogenicity to humans and animals, has attracted more and more attention in the past 40 years. In the study of the biological detoxification of aflatoxin B1—although it has been confirmed that Kocuria rosea has the ability to efficiently remove aflatoxin B1—the degradation products, degradation pathways, and toxicity of the degradation products of aflatoxin B1 have not been clarified. Therefore, in this study, it was found that the functional groups of aflatoxin B1 changed after being cultured with Kocuria rosea, indicating the production of aflatoxin B1 degradation products. Ten main AFB1 degradation products (including aflatoxicol, aflatoxin D1, and aflatoxin D2) were identified, and their structures and fragmentation mechanisms were further elucidated by the parent ions and fragment ions of the products. The possible degradation pathway of aflatoxin B1 was proposed according to the structure of the degradation products. Additionally, the toxicity of the degradation products was analyzed according to the quantitative structure–activity relationship theory, and cytotoxicity experiments and dead–live cell staining experiments showed that the toxicity of the degradation products was significantly less than that of aflatoxin B1. In this study, the mechanism of aflatoxin B1 degradation by Kocuria rosea was explored from several perspectives, indicating that aflatoxin B1 degradation by Kocuria rosea is a promising biological method.